Injectable Bone Substitute Synthesized from Mangrove Snail Shell - Yessie Widya Sari; Reza Pahlevi Rudianto; Nur Aisyah Nuzulia; Sulistioso Giat Sukaryo (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2017)
The need for biomaterials tends to increase especially in the field of medicine caused by cases of increasing bone damage. The biomaterial that is being developed for bone implants is hydroxyapatite (HAp). The high value of imports of bone-replacement biomaterials in Indonesia is conidered as a thoughtful problem because of the high price, therefore the development of biomaterials used as a substitute for bone derived from natural materials. In this study, HAp in the form of an injectable bone substitute (IBS) was syntehsized. IBS is a bone-substitute material in the form of a suspension. IBS can be applied by injection to reach deeper areas of bone defects and be able to adjust the shape of bone or tooth defects properly. HAp was synthesized in this study with assistance of microwave irradiation. Mangrove snail shell was used as calcium sources. Furthermore, this study indicated that HAp synthesized from mangrove snail shell had a high potency to be developed as IBS.